Vanilla (Vanilla planifolia) production in Mexico: analysis and forecast - Luis-Rojas, Samuel; Ramírez-Valverde, Benito; Díaz-Bautista, Maximino; Pizano-Calderón, José; Rodríguez-López, Carmen (Revista Mexicana de Ciencias Agrícolas, 2020)
Vanilla (Vanilla planifolia) is one of the most demanded aromatics in the culinary and soft drink industry, and among licit crops it is the most profitable, only after saffron. In 2017, production in Mexico was 505.32 tons, placing it as the fourth largest producer in the world after Madagascar, Indonesia and China. The objective of this study was to develop a forecast model for annual vanilla production in Mexico (PVAINI). The data were from the period 2000 to 2016 and the Box-Jenkins methodology of integrated autoregressive processes of moving averages (ARIMA) was used. The model parameters were estimated using the maximum likelihood method with the Statistical Analysis System computer package. A model based on the PVAINI series was adapted for the period 2000 to 2016 and validated with the data for the years 2016 and 2017. The best estimated model was ARIMA (1, 1, 1) and indicated that the PVAINI are explained with the production occurred 4 previous years. The predicted values for 2017 were close to the observed values. The ARIMA model represented PVAINI with some precision in the next year and provided information to plan and make decisions for the next six years.